PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL PICTURE AND PICTURE KELAS III SEKOLAH DASAR - Nuriza, Nuriza; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The problem in this study is "Can using the Picture and Picture model improve narrative writing skills of third grade students at 66 Pontianak Elementary School?". The method used is descriptive with Classroom Action Research. Data collection techniques used were Observation and Test with data collection tools namely Observation Sheet and Test usage. The subjects of the study were teacher and class III students totaling 29 people. The results of the third cycle obtained are: 1) The ability of teachers to implement learning cycle I with a value of 2.35 with enough categories, the second cycle has increased from 0.65 to 3.04 which is included in both categories. While the third cycle increased by 0.81 to 3.81 and included in the very good category. 2) Students' narrative writing skills using picture and picture model Cycle I 50.57 increased by 18.39 in cycle II to 68.96 and in cycle III increased by 14.67 to 83.67 which was included in the excellent category. So the conclusion by using picture and picture models in learning Indonesian can improve narrative writing skills. Therefore the picture and picture model can be used to improve students' narrative writing skills.Keywords:Improvement, Narrative Essay, Picture and Picture Models, Writing Skills.